Painting with odors: How olfactory stimuli influence artistic expression, emotional response, visual perception, and object selection - Zahra Davoudi; Nobuyuki Sakai (PLoS ONE, 2026)
In recent years, the relationship between olfaction and vision has received increasing attention. We combined psychology and art to investigate how two specific odors, strawberry and rose, influence visual perception, artistic expression, creativity, and object selection across two studies. In Study 1, 24 participants created paintings inspired by rose and strawberry odors. Sixty additional participants evaluated these paintings using seven semantic differential scales. In the final phase, another 60 participants rated the odors using the same scales. In Study 2, 60 participants were randomly assigned to one of three rooms: a strawberry-odorized room, a rose-odorized room, or a control room with no odor. Five artificial objects (strawberries, lemons, and roses) were placed on a table in each room. Without being told about the presence of odors, the participants were asked to select one object and paint it. Afterward, they reported the odor they perceived and selected the associated colors using a standardized color panel. This design aimed to determine whether specific odors influenced object selection and visual perception. Together, these experiments provide converging evidence suggesting consistent odor-color associations and indicate that odors may influence visual perception and object selection.